Penggunaan alat peraga manipulatif untuk pembelajaran konsep pecahan bagi Guru Matematika Tingkat SMP - Nasrullah Nasrullah; Rusli Rusli; Abdul Abdul (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This paper is the result of the Community Partnership Program (PKM) activity by presenting the use of Acrylic Manipulative Aids (APMA) for learning fraction concepts for math teachers. The purpose of the activity is to maximize active learning activities in the classroom and use teaching aids in mathematics learning activities. The target is for junior high school teachers in Bulukumba District where 21 people are involved in the activity. The form of activities is training, while implementation information is fulfilled by providing worksheets and questionnaires as response sheets for activities. The results of the training activities carried out received a positive response. Not only is APMA considered feasible as a medium of learning or teaching aids, but it can also be used to help students overcome difficulties in learning the concept of fractions, fraction operations consisting of addition, subtraction, multiplication, and division. In addition, by convincing the teacher to respond that APMA can complete the explanations contained in mathematics textbooks. In other words, in addition to learning by using learning resources derived from books, APMA is also useful to supplement the provision of understanding to students in the classroom.